Debris Disk Science with the Palomar ExAO System: First Results. Issue Volume 8:Issue S299(2013) (6th January 2014) - Wahl, Matthew; Metchev, Stanimir; Patel, Rahul; Serabyn, Eugene; Mawet, Dimitri; Dekany, Richard; Roberts, Jennifer; Burruss, Rick; Bouchez, Antonin; Truong, Tuan; Baranec, Christoph; Guiwits, Stephen; et al.
Abstract: We present first imaging results from the PALM-3000 adaptive optics system and PHARO camera on the Hale 5 m telescope. Observations using a vector vortex coronagraph have given us direct detections of the two-ring dusty debris system around the star HD 141569. Our observations reveal the inner clearing in the disk to unprecedentedly small angular separations, and are the most sensitive yet at the H and K bands. We are for the first time able to measure and compare the colors of the scattered light in the inner and outer dust rings, and find that the outer ring is significantly bluer than the inner ring.